Effects of picking methods on the berry production of bilberry (Vaccinium myrtillus), lingonberry (V. vitis-idaea) and crowberry (Empetrum nigrum ssp. hermaphroditum) in Northern Finland - Manninen, Outi H.; Peltola, Rainer
2013